A Case of Concurrent Disseminated Coccidioidomycosis and Embryonal Carcinoma When Lice and Fleas Coexist - Michael Ke MD; Arash Heidari MD; Michael Valdez MD; Allen Tsiyer MD; Rasha Kuran MD; Royce Johnson MD (SAGE Publishing, 2022)
Coccidioidomycosis (CM) is a fungal infection endemic to the southwestern United States with a wide range of clinical presentations depending on the infected organ systems. Most infections are asymptomatic. Coccidioidomycosis causes a primary pulmonary infection and when symptoms occur, they most often resemble community-acquired pneumonia. One percent of cases disseminate, typically via hematogenous or lymphatic spread. It is in these cases that more severe symptoms may present and potentially overlap with those characteristics of other systemic illnesses. This is a case of CM disseminated to lymph nodes in a 24-year-old man with concomitant metastatic embryonal carcinoma. It is difficult to identify the primary etiology for many components of this patient's presentation, including diffuse lymphadenopathy and multiple pulmonary nodules. Furthermore, the relationship between these 2 concurrent disease processes is not entirely clear. Factors that may contribute include the well-known phenomenon of locus minoris resistentiae (LMR) or potentially a shared immune failure between infectious organisms and malignant cells.